A SIMILARITY ANALYSIS TO DETERMINE RACE SEQUENCES IN REGIONAL SWIMMING COMPETITIONS (Fiep Bulletin - online, 2013)
The aim of this study was to present a scientific approach on the organization and sequences of swimming races in the state of Santa Catarina, based on the races by the same swimmer during the 2012 season. Results from 358 individuals, with 243 male and 115 female participants, were obtained from the public database of the Aquatic Federation of Santa Catarina (FASC). These results were filtered according to the best technical score acheived, independent of the race. To analyze the races, a Bray-Curtis similarity matrix was performed to obtain a cluster analysis. This analysis was depicted by a dendogram, determined by the rank similiarity values in the matrix, which calculates the distances between the groupings. For the female competitiors, results presented 3 group formations, formed by similarities between races shown as: All 200 and 400m Breastroke and Medley races in one group; all 400, 800 and 1500m Freestyle, 200m Butterfly, and 400m Medley in another group; and the remaining in the last group. Considering the similarities between races, it is possible to organize the sequence of the competition using a scientific basis that enables swimmers to achieve their best performance.
Keywords: Swimming; Competition; Performance.